2018
DOI: 10.1155/2018/5798265
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Vibration Does Not Seem to Affect Postural Control in Healthy Active Older Women

Abstract: Objective This study investigated the acute residual effects induced by different frequencies of whole-body vibration (WBV) on postural control of elderly women. Design Thirty physically active elderly women (67 ± 5 years) were randomly divided into three groups: two experimental groups (high WBV frequency: 45 Hz and 4 mm amplitude, n = 10; low WBV frequency: 30 Hz and 4 mm amplitude, n = 10) and one control group (n = 10), with no treatment. The participants were first subjected to stabilometry tests and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Moreover, VT has also been shown to improve balance and proprioception, which leads to a reduction in incidents of falling [47,48]. Despite these desirable findings, there are also studies that show controversial results with regard to proprioception [49,50], rate of torque development (RTD) [12], and muscle strength [51][52][53]. To explain the reason for discrepancies, we should pay attention to whether VTs were administered via different application methods (i.e., duration, amplitude, and frequency).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VT has also been shown to improve balance and proprioception, which leads to a reduction in incidents of falling [47,48]. Despite these desirable findings, there are also studies that show controversial results with regard to proprioception [49,50], rate of torque development (RTD) [12], and muscle strength [51][52][53]. To explain the reason for discrepancies, we should pay attention to whether VTs were administered via different application methods (i.e., duration, amplitude, and frequency).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that suprathreshold vibration has a positive effect on decreasing the incidence of muscle fatigue[ 33 - 35 ]. Other studies found that suprathreshold vibration has a nonsignificant effect[ 36 , 37 ] and may lead to harmful effects. Furthermore, a recent meta-analysis reported that the available studies on suprathreshold muscle tendon vibration after stroke are low in their methodological qualities and additional studies of high methodological quality are required to achieve a strong agreement concerning muscle tendon vibration intervention protocols and their recommendation in clinical settings[ 38 ].…”
Section: Introductionmentioning
confidence: 99%